(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This review presents research on structural and functional features of mammary gland parenchymal and stromal components; importance of the mammary gland in the adoptive immunity transfer to a newborn, particularly immune humoral and cellular components transmitted from mother to baby.